Cosmopolitanism, Markets, and Consumption A Critical Global Perspective (Springer International Publishing, 2018)
This book addresses the complicated question of how markets and consumption create the possibilities for cross-cultural exchanges and the multicultural pleasures of omnivorous consumption, whilst at the same time building new boundaries and distinctions, paving the way for new exploitative relationships, and initiating novel modes of status and capital accumulation. The contributors identify that the divide between the economic and ethical dimensions of globalisation has never seemed in sharper relief. With the workings of global markets at odds with fostering cosmopolitan social change, this collection addresses the question of whether we should assume that market logics and consumptive practices conflict with cosmopolitan agendas. It also explores whether the imperatives of economic globalisation and individual consumption practices are opposed to cosmopolitan prospects for global solidarities. Cosmopolitanism, Markets and Consumption will be of interest to students and scholars with interests across a range of disciplines including in the social sciences, businesses and marketing studies.